Preserving and documenting the Cultural Heritage - Özkut, Deniz (Enquiry The ARCC Journal for Architectural Research, 2008)
The phenomenon of preservation may be described as a physical process that depends onconceptual facts. When observed from a conceptual point of view, ‘values' cause the divergencesin the preservation process, which could be named as the pre-requisites of the construction.Values carry emotional and physical points of view. The emotional context, of course, dependson recognizing and remembering while physical context depends on direction of research. They are indicators of cultural characteristics and historical identity. ‘Cultural values'1, more over, explains the meanings attributed to the cultural property, which meanings will be preserved, and the reasons for their preservation. On behalf of this context, the preservation process may be defined as the preservation of the cultural heritage within an effective system. This effective system isaimed at attaining the total quality as a result of a synthesis of the technology, technique, and material originally deployed with those of the present. Besides, one of the most important inputin the preservation process is the priorities of the intervention to be held, as the latter will determine the decisions and types of intervention during the implementation phase of the preservation project. As a significant paradox, the most important parameter that shapes both a preservationproject and its process appears to be the risks that consist of indefinite input preventing theproject from a proper definition of its context. Since all physical problems and the social statusof the cultural property to be preserved have direct impact upon the design process of thepreservation project, these priorities and the risks should be clarified in the course of pre-assessment phase at the beginning of the preservation process.